Interactive Effects of Hypoxia and Temperature on Coastal Pelagic Zooplankton and Fish - Roman, Michael R.; Brandt, Stephen B.; Houde, Edward D.; Pierson, James J. (Frontiers in Marine Science, 2019)
Hypoxia, triggered in large part by eutrophication, exerts widespread and expanding stress on coastal ecosystems. Hypoxia is often specifically defined as water having dissolved oxygen (DO) concentrations < 2 mg L-1. However, DO concentration alone is insufficient to categorize hypoxic stress or predict impacts of hypoxia on zooplankton and fish. Hypoxic stress depends on the oxygen supply relative to metabolic demand and water temperature controls both oxygen solubility and the metabolic demand of aquatic ectotherms. Accordingly, to assess impacts of hypoxia requires consideration of effects of temperature on both oxygen availability and animal metabolism. Temperature differences across ecosystems or across seasons or years within an ecosystem can dramatically impact the severity of hypoxia even at similar DO concentrations. Low DO can have various non-lethal outcomes for pelagic zooplankton and fish depending on temperature and the physiological tolerances of impacted species. Living under sub-optimum DO can reduce temperature-dependent metabolic efficiencies, prey capture efficiency, growth and reproductive potential, thus impacting production and individual zooplankton and fish fitness. Avoidance of hypoxic bottom water can reduce or eliminate low-temperature thermal refuges for organisms and increase energy demands and respiration rates, and potentially reduce overall fitness if alternative habitats are sub-optimal. Moreover, differential habitat shifts among species can alter predator-prey interactions and modify food webs. For example, more tolerant zooplankton prey may use hypoxic waters as a refuge from fish predation. In contrast, zooplankton avoidance of hypoxic bottom waters can result in prey aggregations at oxyclines sought out by fish predators. Hypoxic conditions that affect spatial ecology can drive taxonomic and size shifts in the zooplankton community, affecting foraging, consumption and growth of fish. Advances in understanding the ecological effects of low DO waters on pelagic zooplankton and fish and comparisons among ecosystems will need to develop generic models and robust metrics that include thermal conditions of hypoxic waters and adjacent habitats.